(untitled) (Third Sector Social Economic Review, 2018)
As competition and the market begin to be compared to battlefields, it seems that the research of adapting military strategies to competition strategies is increasingly seen. From this point of view, the principles of Sun Tzu, the military and strategy expert who is the author of the oldest and most valuable military strategy book, ""The Art of War"", has begun to be used in many business areas. Since he integrates elements of the competition effectively, it is suggested that the principles of Sun Tzu will be useful in identifying competition strategies for businesses and especially SMEs which are seen as disadvantaged in competition According to Sun Tzu, before any action is taken, five important factors must be examined. They are the way (moral impact), weather, terrain, commander, and discipline. These five factors, identified as the strategic contingency, together with strategic leadership practices help identify the strengths and weaknesses of the business. As a result, the business can choose between ""avoiding the fight"" or ""battle to win"" strategies, to the extent that it has strengths